2004
DOI: 10.1099/mic.0.26778-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of genetic polymorphisms affecting the four phospholipase C (plc) genes in Mycobacterium tuberculosis complex clinical isolates

Abstract: The Mycobacterium tuberculosis genome contains four highly related genes which present significant similarity to Pseudomonas aeruginosa genes encoding phospholipase C enzymes. Three of these genes, plcA, plcB and plcC, are organized in tandem (locus plcABC). The fourth gene, plcD, is located in a different region. This study investigates variations in plcABC and plcD genes in clinical isolates of M. tuberculosis, Mycobacterium africanum and 'Mycobacterium canettii '. Genetic polymorphisms were examined by PCR,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 44 publications
(45 reference statements)
2
32
1
Order By: Relevance
“…Previous investigations of the genetic diversity of M. tuberculosis plc genes used either convenience samples or selected samples (7,18,21,25). In our population-based sample, we observed that the plcD mutation accounted for 88% (233/266) of the mutations found in the plc genes; this is consistent with the previous findings of Talarico and colleagues, who used a convenience sample collected from Turkey (18).…”
Section: Vol 43 2005 Relevance Of M Tuberculosis Plc Gene Mutationsupporting
confidence: 82%
See 3 more Smart Citations
“…Previous investigations of the genetic diversity of M. tuberculosis plc genes used either convenience samples or selected samples (7,18,21,25). In our population-based sample, we observed that the plcD mutation accounted for 88% (233/266) of the mutations found in the plc genes; this is consistent with the previous findings of Talarico and colleagues, who used a convenience sample collected from Turkey (18).…”
Section: Vol 43 2005 Relevance Of M Tuberculosis Plc Gene Mutationsupporting
confidence: 82%
“…tuberculosis clinical strains with major polymorphisms in all four plc genes and impaired plc gene expression have been reported previously by others (25). Raynaud et al recently demonstrated that plcABC triple mutants and plcABCD quadruple mutants were attenuated for growth in the lungs and spleens of mice, and the expression of the different plc genes was important for virulence at different time points of the infection (13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of these LSP groups (LSP A) comprising four loci was judged to be suitable for phylogenetic interpreations, while other LSPs occurred in regions subject to selection (rich in PE and PPE genes). Association of genotype to phenotype was indicated for deletion in plcD [68]; extrapulmonary TB was two fold more likely with plcD mutant strains [69].…”
Section: Genetics Of Natural Populations Of M Tuberculosismentioning
confidence: 99%